A dinâmica territorial brasileira e a inversão da "tese da fronteira" na porção sul do novo mundo - César Ricardo Simoni Santos (Revista de Geografía Norte Grande)
It is a generally acknowledged fact that the dynamics of frontier advance deeply influenced the broad experience of American post colonial societies. The colonization, which started most from the east boundaries of the continent, appropriated and gradually transformed the American territories from east to west. The advance, initially represented by the arrival of the European settlers, went on to become an important trace of that society which did not come to know any physical limits of a restricted territory. However, despite the common identity granted by these territorial dynamics, the later developments and consequences seem to have shaped differently the Northern representatives from their Southern counterparts. In addition, the interpretation of these facts bore in each of these regions different meanings and traits.